Optimization of hanger arrangement in pedestrian tied arch bridge with sparse hanger system. Issue 12 (September 2019) - Tan, Yonggang; Yao, Yuanbin
The hanger arrangement has a decisive influence on the mechanical behavior of the tied arch bridge with network hanger system. Many investigations on highway or railway tied arch bridges show that the arch bridges with dense network hangers are superior to those with vertical hangers under larger live load. However, numerous dense inclined hangers lower the esthetic effect of the bridge, especially for pedestrian tied arch bridges. Consequently, the sparse inclined hanger system is recommended in the design of pedestrian tied arch bridges. However, the amount of possible schemes of the hanger arrangement grows rapidly with the number of hangers increasing beyond 10, rendering great difficulties in searching for proper schemes. In this article, a dimensionless optimization approach based on genetic algorithm is proposed in searching for hanger arrangement schemes. Numerical analysis indicates that the proposed method is effective in the optimization of pedestrian tied arch bridge with sparse inclined hanger system, and some of the feasible hanger arrangement solutions show more excellent mechanical properties.